The Corporate Permeation Index - A tool to study the macrosocial determinants of Non-Communicable Disease - Joana Madureira Lima; Sandro Galea (Elsevier, 2019)
Commercial interests have long been identified as a macrosocial determinant of health. We present a composite indicator of corporate permeation- the Corporate Permeation Index (CPI) -, a novel tool for explaining variations in the consumption of products such as alcohol or tobacco and in the comprehensiveness of health policy regarding these products.Using a published framework for the analysis of commercial influences on health as a theoretical basis, we collected 25 indicators of corporate permeation comparable across 148 countries in five continents for six years 2010-2015. Two alternative approaches were used in each of the steps taken to build the measure - imputation of missing data, multivariate analysis, and weighing and aggregation of the subcomponents. We assessed the Index's criterion-related validity by calculating the strength of the association among the different formulations of the Index.Alternative formulations of the CPI are highly correlated. Whilst High Income Countries are generally overrepresented among the lowest scores, some High Income Countries have high permeation scores. There is no clear regional pattern, with scores showing as much intra-regional as inter-regional variability.The CPI appears to be a robust measure of corporate permeation at the national level, suggesting tremendous variability in permeation worldwide. There are limitations to the CPI, the most notable of which is the lack of large scale cross-country comparable data on some important mechanisms of corporate permeation (e.g., lobbying expenditures by large corporations). Further work will target proxy measures for these phenomena to be incorporated in the Index calculation. Keywords: Commercial determinants of health, Macrosocial Determinants of Health, Non Communicable Diseases, Corporate power